Differences in attitudes towards immigration between Australia and Germany: The role of immigration policy. - Ueffing, Philipp; Rowe, Francisco; Mulder, Clara H. (Bundesinstitut für Bevölkerungsforschung, 2015)
This paper investigates the connection between national immigration policy and a society's attitudes towards immigration. It argues that a country's immigration policy framework plays an important role in the formation of attitudes towards immigration by shaping the local national context of the receiving country. It examines the influence of a country's immigration policy framework by contrasting two countries - Australia and Germany - that developed remarkably different immigration policies in response to large immigration movements during the postwar period. We explore attitudes towards immigration on four dimensions: (1) the national economy, (2) the labour market, (3) the national culture, and (4) the level of immigrant influx. The analyses reveal three main findings. First, people in Australia tend to display more positive attitudes towards immigration than in Germany. Second, in both countries, attitudes towards immigration tend to be influenced in a similar way by an individual's socio-economic background and feelings of national identity (in the form of nationalism and patriotism). Third, immigration policy represents a strong indicator of attitudes towards immigration. We found that the planned integrative immigration policy in Australia supports the formation of more positive attitudes towards immigration by infl uencing people's perception on the economic and socio-cultural impacts of immigration.
Keywords: Bevölkerungsentwicklung; Einwanderung; Arbeitsmarkt; Gesellschaft; Kultur; Einstellung; Einwanderungspolitik; Politikfolgenabschätzung; Zuwanderung; Akzeptanz; Nationale Identität; Internationaler Vergleich